COPY NUMBER VARIATIONS ON CHROMOSOME 15 DETECTED BY MOLECULAR KARYOTYPING IN PATIENTS WITH DEVELOPMENTAL DELAY AND CONGENITAL ANOMALIES: / - Beronja, Branko; Đuranović, Ana (Medicinski podmladak, 2024)
Introduction: Global developmental delay (GDD) and congenital anomalies represent a heterogeneous group of medical conditions that may have a known genetic etiology. Molecular karyotyping is the gold standard for detecting copy number variations (CNV), and the first-line test in patients with GDD and congenital anomalies, with an average diagnostic yield of 15%. Chromosome 15 (C15) is one of the chromosomes on which CNV occur most frequently. Aim: to analyze all detected non-polymorphic (significant) CNVs on C15 in patients with GKR and/or congenital anomalies, estimate their share in the overall CNV detection rate of different pathogenicity classes, and present several illustrative cases. Material and methods: In the total sample of 350 patients analyzed by molecular karyotyping technique, 92 with detected significant CNV were singled out. Then, all patients with variants on C15 were analyzed, which were further classified according to type, size, and clinical significance. Results: In 11 patients, at least one significant CNV was detected on chromosome 15, which is 3.15% of the total sample and 11.96% on a sample of patients with significant CNV of any localization. In 72.7% cases CNV was described as pathogenic or likely pathogenic and in 27.3% as a variant of unknown significance. In the total detection rate of csCNV from all chromosomes 15.4%, the share of variations from C15 was 17.2% . Conclusion: The detection rate of csCNVs on C15 in diagnostic yield of the molecular karyotypisation of the patients with GDD and congenital anomalies is 17.2%. , which confirms their significant portion in the etiology of these disorders.